Strategic Enhancement of Financial Inclusion through Shariah-Compliant Fintech: A SWOT Analysis of Bank Syariah Indonesia KCP Gunung Tua - Risma Haryani Siregar; Muhammad Syahbudi; Muhammad Ikhsan Harahap (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
This research aims to determine the strategy for increasing inclusive finance through Shariah fintech at Bank Syariah Indonesia KCP Gunung Tua using SWOT analysis. A qualitative research approach was utilized. The results of the SWOT analysis revealed that the IFAS matrix scored 0.6 and the EFAS matrix scored 0.54, indicating Quadrant I and suggesting an aggressive strategy that supports growth policies by leveraging all strengths to maximize opportunities. Based on these results, the improvement strategy for BSI KCP Gunung Tua includes: first, utilizing transaction services available anytime and anywhere to attract individuals who prefer mobile banking (BSI Mobile) (S3, O3); second, capitalizing on the predominantly Muslim community in Gunung Tua, which has great potential, by offering low operational cost services from the Indonesian Shariah bank (S1, O1); third, leveraging the preference for mobile banking transactions with an easy process at BSI (S2, O3)